2009
DOI: 10.1007/s11046-009-9262-0
|View full text |Cite
|
Sign up to set email alerts
|

Presence of C. albidus, C. laurentii and C. uniguttulatus in Crop and Droppings of Pigeon Lofts (Columba livia)

Abstract: Columba livia is an important reservoir and carrier of Cryptococcus neoformans, Cryptococcus uniguttulatus, Cryptococcus laurentii and Cryptococcus albidus. Upper digestive tract of this species is also known as a habitat for Cryptococcus neoformans. Given the increasing clinical interest of this microorganism, 331 swabs from crop and 174 dropping samples from pigeon lofts in Grand Canary Island have been studied. The obtained results show an extensive presence samples 81 positive (24.47%) of Cryptococcus spp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
0
17
1
3
Order By: Relevance
“…Other yeasts, such as Rhodotorula and Trichosporon, can cause blood infections in patients with indwelling central venous catheters and cancer (Cafarchia et al 2006). Several studies have confirmed the role of pigeon in the epidemiology of these opportunistic pathogen agents causing human infection due to inhalation or contact with their dried feces (Andrade-Silva et al 2010, Rosario et al 2010. In the present work, not all isolates of yeasts evidenced by biochemical test were confirmed and/or detected by MALDI TOF MS.…”
Section: Discussioncontrasting
confidence: 45%
“…Other yeasts, such as Rhodotorula and Trichosporon, can cause blood infections in patients with indwelling central venous catheters and cancer (Cafarchia et al 2006). Several studies have confirmed the role of pigeon in the epidemiology of these opportunistic pathogen agents causing human infection due to inhalation or contact with their dried feces (Andrade-Silva et al 2010, Rosario et al 2010. In the present work, not all isolates of yeasts evidenced by biochemical test were confirmed and/or detected by MALDI TOF MS.…”
Section: Discussioncontrasting
confidence: 45%
“…Thus, pigeons harbouring having thermal‐tolerant yeasts could be a source of continuous spread of these pathogens. However, the survival capability of yeasts in pigeon cloacae is unclear (Littman and Borok 1968; Rosario et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most C. laurentii isolates described around the world have been identified by morphological criteria, which can miss subtle differences and misidentify cryptic species [1], [14], [15]. Unlike C. neoformans and C. gattii , few studies have applied DNA sequencing to describe the molecular phylogeny of C. laurentii [11], [16], [17].…”
Section: Introductionmentioning
confidence: 99%